Implementation of the Know Want Learn Strategy to Improve Elementary School Students' Reading Comprehension Skills - Angga Ramdani; Mislan Mislan; Ika Panggih Wahyuningtyas (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to describe the implementation of the Know-Want-Learned (KWL) strategy in improving the reading comprehension skills of fifth-grade students at SDN 67/VI Tanjung Gedang and to identify the improvement after its implementation. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 25 fifth-grade students. Data were collected through observation, interview, and documentation. The results showed that the implementation of the KWL strategy was able to improve students' reading comprehension skills. This is evidenced by the increase in learning mastery from 28% in the pre-action stage to 65.6% in Cycle I, and further increased to 87.2% in Cycle II. Therefore, the KWL strategy is considered effective in improving students' reading comprehension skills.